Diversity and composition of beetles (Order: Coleoptera) in three different ages of oil palms in Lekir Oil Palm Plantation, Perak, Malaysia - Luqman Hakim Azhari,; Noor Nasuha A. A.,; Dzulhelmi M. N.,; Nurul Fatihah A. L.,; Muhamad Fahmi M. H.,; Teo, T. M.; Idris Abd. Ghani,; Izfa Riza Hazmi, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
The diversity and composition of beetles from oil palm plantation in Ladang Lekir, Perak, Malaysia were collected each month using Malaise trap, yellow pan and window traps from three different sites on the basis of their oil palm aged i.e. five (Plot 1), seven (Plot 2) and 12 (Plot 3) years old from November 2015 to October 2016. From 3862 individuals, 110 species and 83 morphospecies from 40 families and 59 subfamilies were successfully collected. From all samples recorded, the five years old oil palm showed the highest Shannon Diversity Index (H' = 3.42), Peilou Equality Index (E' = 0.23) and Margalef Richness Index (R’= 17.33) with species accumulation curve near to asymptote. The most abundant species recorded from the three sites was Elaeidobius kamerunicus with 940 individuals (relative abundance, RA = 24%). Plot 1 had the highest beetle species with 132 individuals (68.4%), while Plot 2 was the lowest with 85 individuals (44%). The t-test analysis showed that there was no significant difference in term of the diversity index (H’) between Plot 3 and Plot 2 (p-value=0.092), while there were significant differences between these two plots (Plot 2 and Plot 3) with Plot 1 (p-value= 0.47 and 0.046). This study would provide basic information for future research in sustainable oil palm plantations management in Malaysia.